Development and efficacy of a novel live-attenuated QX-like nephropathogenic infectious bronchitis virus vaccine in China. Issue 9 (25th February 2015) - Feng, Keyu; Xue, Yu; Wang, Jinglan; Chen, Weiguo; Chen, Feng; Bi, Yingzuo; Xie, Qingmei
Highlights We developed a live vaccine strain YX10p90 by passaging through chicken embryos. YX10p90 could provide better protection against the QX-like IBV in China. Amino acid substitutions and a deletion in the 3'-UTR may involve in attenuation.